(untitled) (Social and Environmental Law Journal, 2025)
This article revolves around the central theme of agroecology from a legal perspective. Agroecology is a concept that seeks to align agricultural production with environmental preservation. The objective is to discuss how this practice can contribute to sustainability in agriculture through the use of more natural techniques that respect ecological balance. This work was conducted based on literature review and data analysis. In conclusion, we found that agroecology is an important tool for environmental preservation and conscious production, aiming to produce without harm, protect fauna, flora, water resources, promote local economy, and produce healthier foods, all of which are protected by regulations and laws.